A comparison of continuous cold flow and compression device and traditional icing regimen and no icing following anterior cruciate ligament reconstruction: a pilot study - Butt, Umerr; Iqbal, Javed; Shah, Imran Ali; Khan, Zainab Aqeel; Vuletic , Filip; Mohsin , Areeb (Journal of the Pakistan Medical Association, 2023)
The aim of this study was to investigate the effectiveness of continuous cold flow and compression device as against traditional icing regimen and without icing after anterior cruciate ligament (ACL) reconstruction. All patients undergoing ACL reconstruction from June 2021 to August 2021 were enrolled in this study. Patients were randomly allocated to three groups: A control group (n=10) with no ice regimen post-operatively, a second control group (n=10) with ice bag, and a third group (n=10) with continuous cold flow and compression device (physiolab). All patients who had isolated ACL tear evident on magnetic resonance imaging were included. Pain intensity, limb girth, Oxford Knee Score, and 12-item survey form were measured pre- and post-operatively. Significant difference was noted between pain scores in all groups at two- and six-week follow-ups with p-value of 0.004 and 0.01. —Continue